Long-Term Anticholinergic, Benzodiazepine and Z-Drug Use in Community-Dwelling Older Adults: What is the impact on Cognitive and Neuropyschological Performance? - Mc Carroll, Kevin; Cunningham, Conal; Dyer, Adam (My University, 2021)
Background: Long‐term use of anticholinergics, benzodiazepines and related drugs (or “Z‐drugs”) have been associated with cognitive impairment and dementia. However, the relationship of these medications with cognitive function and domain‐specific neuropsychological performance in older adults without dementia, is unclear. Methods: 5135 older adults (74.0 ± 8.3 years; 67.4% female) without a diagnosis of dementia were recruited in Ireland to the Trinity‐Ulster‐Department of Agriculture (TUDA) study. Detailed cognitive and neuropsychological assessment was conducted using the Mini‐Mental State Examination (MMSE), Frontal Assessment Battery (FAB) and Repeatable Battery for Assessment of Neuropsychological Status (RBANS). Results: A total of 44% (2259 of 5153) used either a potential or definite anti-cholinergic medication. Overall, 9.7% (n = 500) used a definite anticholinergic medication. Regular benzodiazepine use was reported by 7% (n = 363), whilst 7.5% (n = 387) used a “Z‐drug”. Use of definite, but not potential anticholinergic medication was associated with poorer performance on all three assessments (β: −0.09; 95% CI: −0.14, −0.03, p = 0.002 for MMSE; β: −0.04; 95% CI: −0.06, −0.02; p < 0.001 for FAB; β: −4.15; 95% CI: −5.64, −2.66; p < 0.001 for RBANS) in addition to all domains of the RBANS. Regular benzodiazepine use was also associated with poorer neuropsychological test performance, especially in Immediate Memory (β:−4.98; 95% CI: −6.81, −3.15; p < 0.001) and Attention (β: −6.81; 95% CI: −8.60, −5.03; p < 0.001) RBANS domains. Conclusions: Regular use of definite anticholinergic medications and benzodiazepines, but not potential anticholinergics or “Z‐drugs”, was associated with poorer overall and domain‐specific neuropsychological performance in older adults.
PUBLISHED
Keywords: anticholinergic medication; benzodiazepine; cognition; older adults